Promoting Latinx health equity through community-engaged policy and practice reforms in North Carolina - Thoumi, Andrea; Plasencia, Gabriela; Madanay, Farrah; Ho, Ethan Shih-An; Palmer, Caroline; Kaalund, Kamaria; Chaudhry, Nikhil; Labrador, Amy; Rigsby, Kristen; Onunkwo, Adaobi; Almonte, Ivan; Gonzalez-Guarda, Rosa; et al. (Frontiers in Public Health, 2023)
The Latinx Advocacy Team & Interdisciplinary Network for COVID-19 (LATIN-19) is a unique multi-sector coalition formed early in the COVID-19 pandemic to address the multi-level health inequities faced by Latinx communities in North Carolina. We utilized the National Institute on Minority Health and Health Disparities (NIMHD) Research Framework to conduct a directed content analysis of 58 LATIN-19 meeting minutes from April 2020 through October 2021. Application of the NIMHD Research Framework facilitated a comprehensive assessment of complex and multidimensional barriers and interventions contributing to Latinx health while centering on community voices and perspectives. Community interventions focused on reducing language barriers and increasing community-level access to social supports while policy interventions focused on increasing services to slow the spread of COVID-19. Our study adds to the literature by identifying community-based strategies to ensure the power of communities is accounted for in policy reforms that affect Latinx health outcomes across the U.S. Multisector coalitions, such as LATIN-19, can enable the improved understanding of underlying barriers and embed community priorities into policy solutions to address health inequities.